Survey of need for death preparatory education among health care providers assisting - Ahn, Youngmi; Jung Yoo, Eun (Opción, 2019)
This study seeks to investigate the purpose in life, fear of death and dying, death-related experiences, and the need for death education experienced by health care providers via a descriptive research design method. As a result, 86.98% of medical staff answered that they did not receive death related education. In conclusion, the health statistics connected to the annual deaths have treated death as a medical failure that did not resolve the disease rather than associating it with human finitude.